RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera - Chikate, Yojana R.; Dawkar, Vishal V.; Barbole, Ranjit S.; Tilak, Priyadarshini V.; Gupta, Vidya S.; Giri, Ashok P. (Pesticide Biochemistry and Physiology, 2016)
Helicoverpa armigera is one of the major crop pests and is less amenable to current pest control approaches. RNA interference (RNAi) is emerging as a potent arsenal for the insect pest control over current methods. Here, we examined the effect on growth and development in H. armigera by targeting various enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine protease like cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b) through dsRNA approach. Significant downregulation of cognate mRNA expression and reduced activity of trypsin and GST-like enzyme were evident upon feeding candidate dsRNAs to the larvae. Among these, the highest mortality was observed in HaAce4 dsRNA fed larvae followed by HaJHE; HaCAT; HaCuZnSOD; HaFabp and HaTry3 whereas remaining ones showed relatively lower mortality. Furthermore, the dsRNA fed larvae showed significant reduction in the larval mass and abnormalities at the different stages of H. armigera development compared to their control diets. For example, malformed larvae, pupae and moth at a dose of 60 pg/day were evident in high number of individual insects fed on dsRNA containing diets. Moreover, the growth and development of insects and moths were retarded in dsRNA fed larvae. These findings might provide potential new candidates for designing effective dsRNA as pesticide in crop protection. (C) 2016 Elsevier Inc. All rights reserved.